2012
DOI: 10.1524/ract.2012.1975
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of tetravalent thorium by geomedia

Abstract: We measured the pH-dependent adsorption of Th(IV), an analogue for Pu(IV) and other tetravalent actinides, to two geomedia: goethite (α-FeOOH(s)) and a heterogeneous Fe-containing sand from the southeastern USA. The goal was to examine whether or not the Th(IV)-goethite adsorption data could be used to predict the adsorption of Th(IV) by the heterogeneous sand. In the absence of either geomedia, after forty-eight hours the measured pH-dependent “adsorption” was consistent with the solubility of solid amorphous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…232 Th Series partitioning. The parent and supporting isotope in the natural Th decay series, 232 Th ( t 1/2 = 1.4 × 10 10 years), is not expected to undergo oxidation/reduction reactions under natural conditions at depth in the formation, but is nonetheless particle reactive and insoluble in environmental waters and brines ( Melson et al 2012 ). Accordingly, we observed exceedingly low concentrations of 232 Th in unfiltered Marcellus Shale produced fluids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…232 Th Series partitioning. The parent and supporting isotope in the natural Th decay series, 232 Th ( t 1/2 = 1.4 × 10 10 years), is not expected to undergo oxidation/reduction reactions under natural conditions at depth in the formation, but is nonetheless particle reactive and insoluble in environmental waters and brines ( Melson et al 2012 ). Accordingly, we observed exceedingly low concentrations of 232 Th in unfiltered Marcellus Shale produced fluids.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the geologic history and reducing (anoxic) conditions at depth in the Marcellus Shale formation, parent and supporting radionuclide 238 U (which, unlike 232 Th, can be redox active under natural conditions) is likely to be contained in the crystal lattice of minerals or adsorbed to solid phase structures in a reduced highly insoluble (+4) oxidation state ( Swanson 1961 ) ( Figures 1 and 3 ). Thus, geochemical conditions favor adsorption of 238 U and decay-product actinides ( 234 Th, 234 Pa, and 234 U) to interstitial surfaces of surrounding minerals ( Figures 1 and 3 ) ( Melson et al 2012 ), and these radionuclides are likely fixed at depth. In support of these assertions, we observed exceedingly low concentrations of U and Th radionuclides in unfiltered produced fluids from Marcellus Shale ( Tables 1 and 2 ; see also Supplemental Material, “Uranium absent”).…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory batch experiments investigating Th sorption to hematite (Fe 2 O 3 ) systems (Cromieres et al, 1998;Melson et al, 2012) have shown that interactions are strong with a sorption edge near pH 3. Pu exhibits similarly strong sorption to iron oxide minerals and the tetravalent oxidation state dominates at equilibrium due to surface mediated reduction (Sanchez et al, 1985 days leading to the conclusion that there is a strong irreversibly sorbed fraction of Pu (Lu et al, 1998;Lu et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Performance assessment calculations for hypothetical high-level radioactive waste (HLW) repositories [1] show that 229 Th which is a member of the neptunium series (4n+1) is one of the radionuclides dominating the long-term radiological hazard. Thorium exists only in the tetravalent oxidation state independent of the redox conditions of groundwater [2,3] and is often considered as an analog of other tetravalent actinide elements (U, Np and Pu) [4,5]. The dominant aqueous species of Th in reference groundwaters for the performance assessment [1,6] were estimated to be hydroxo-carbonate complexes from thermodynamic calculations [7].…”
Section: Introductionmentioning
confidence: 99%